Chloramphenicol-Induced Changes in the Synthesis of Ribosomal, Transfer, and Messenger Ribonucleic Acids in Escherichia coli B/r - Shen, V. (1977)
The synthesis of ribosomal ribonucleic acid (rRNA), transfer RNA (tRNA) and messenger RNA (mRNA) was measured in Escherichia coli B/r after the addition of 100 μg of chloramphenicol (CAM) per ml to cultures growing either in one of three minimal media (succinate, glycerol, or glucose) or in one of the same three media supplemented with 20 amino acids. (i) During CAM treatment, rRNA and tRNA were synthesized in the same relative proportions (85:15) as during exponential growth. The faster accumulation of tRNA relative to rRNA in CAM was due to a decreased stability of rRNA that is synthesized in the presence of or immediately before the addition of CAM. (ii) CAM stimulated the synthesis of rRNA and tRNA two- to eightfold. The results fell into two groups; one group was from studies done in minimal media and the other was from amino acid-supplemented media. In each group the stimulation decreased with increasing growth rate of the culture during exponential growth before the addition of CAM; however, the stimulation in minimal media was lower than that in amino acid-supplemented media. (iii) CAM caused an increase in the proportion of rRNA and tRNA synthesis and a corresponding decrease in the proportion of mRNA synthesis. In minimal media, the residual proportion of mRNA synthesis after CAM treatment was 10 to 15% of total RNA synthesis; in amino acid-supplemented media this proportion was 0 to 10%. In either case, the residual proportion of mRNA synthesis was independent of the proportions observed during exponential growth in these media. (iv) The absolute rate of mRNA synthesis decreased severalfold with the addition of CAM; i.e., the rate of synthesis of rRNA and tRNA was increased at the expense of mRNA synthesis. (v) During exponential growth, the fraction of the instantaneous rate of total RNA synthesis that corresponds to mRNA is a function of both the growth rate and the presence or absence of amino acids in the growth medium: in the absence of amino acids, this fraction decreased with increasing growth rate; in the presence of amino acids, the fraction increased slightly with growth rate. These results are consistent with a regulation of rRNA and tRNA synthesis at the transcriptional level, e.g., with a CAM-induced increase in the affinity of RNA polymerase for the rRNA and tRNA promoters. The results also suggest the occurrence of a regulation of RNA polymerase enzyme activity, i.e., of an activation of RNA polymerase that is inactive during exponential growth. A distinction between these alternatives requires measurements of the rRNA chain growth rates during CAM treatment.